Cyclopentannulated Dihydrotetraazapentacenes. Issue 12 (2nd February 2022) - Heckershoff, Robin; Maier, Steffen; Wurm, Thomas; Biegger, Philipp; Brödner, Kerstin; Krämer, Petra; Hoffmann, Marvin T.; Eberle, Lukas; Stein, Jana; Rominger, Frank; Rudolph, Matthias; Freudenberg, Jan; et al.
Abstract: The transition‐metal‐catalyzed cyclization of bissilylethynylated N, N '‐dihydrotetraazapentacene (TIPS‐TAP‐H2 ) into bissilylated cyclopenta[ fg, qr ]pentacenes is reported. Depending on the catalyst either none, one or two silyl groups migrate and change their positions in the formed five‐membered rings. The optoelectronic properties are quite similar, whereas the packing motifs differ dramatically. Control experiments and quantum chemical calculations were performed to investigate the mechanism of the reaction and the selectivity of the silyl shift. Abstract : The alkyne units of bissilylethynylated N, N' ‐dihydrotetraazapentacene are transferred into a dihydrotetraazapentacene core by a transition‐metal‐catalyzed cycloisomerization reaction to form a new type of cyclopentannulated tetraazapentacene. Depending on the applied catalyst systems, either silyl group retention or migration takes place, which gives rise to constitutional isomers that show comparable optoelectronic properties but completely different packing motifs in the solid states.